Developing a Professional Judgment Framework for Implementing the Fair Value Standard - Zahra Aslani; Ghasem Blue (بررسی‌های حسابداری و حسابرسی)
Objective The transition toward International Financial Reporting Standards (IFRS) has emphasized the role of fair value in financial reporting. To determine fair value in financial reports, preparers rely on observable market-based inputs and unobservable inputs derived from the reporting entity’s assumptions. Given the extensive reliance on professional judgment in determining fair value, particularly following the approval of Iranian Accounting Standard No. 42, and the lack of operational guidelines for its implementation, this study aims to develop a systematic framework for professional judgment in fair value measurement to enhance the preparation of financial information in Iran. Methods This study utilized a combination of systematic literature review and fieldwork methods. Data were collected through semi-structured interviews with 10 Iranian accounting and auditing experts from four groups—valuers, auditors, preparers, and regulators—conducted between the beginning and end of August 2023. Additionally, a structured questionnaire based on fuzzy logic was administered to 30 experts from the same groups, and the Delphi method was applied to analyze the results. The Best-Worst Method (BWM) was also used to assess the significance and prioritize the components of the framework with input from 8 experts. The Kruskal-Wallis statistical test was employed to compare the views of the four groups, and follow-up interviews with 5 experts were conducted to evaluate the internal validity of the findings. Results The study resulted in developing a professional judgment framework for implementing Iranian Accounting Standard No. 42 (Fair Value Measurement). The framework comprises the following key components: (1) Identifying the scope of the judgment, (2) Evaluating accounting and auditing guidelines, (3) Collecting relevant information and analyzing them, (4) Concluding and making a judgment, and finally (5) Documenting the rationale of professional accounting judgment. Conclusion Professional judgment is a crucial skill for preparers, auditors, and regulators of financial statements, particularly under a principles-based accounting regime. However, making such judgments can be challenging, and there is not always a single correct answer. Also, fair value measurement inherently involves judgment, which introduces the potential for bias in financial statements. A structured professional judgment framework is recommended to improve the quality of financial reporting. This framework includes identifying the judgment scope, evaluating accounting and auditing guidelines, gathering relevant information, forming judgments, and thoroughly documenting them. The credibility and utility of financial reporting are highly dependent on sound judgments, particularly as business transactions become increasingly complex. Moreover, the ability to demonstrate that judgments are reasonable at the time of reporting, given the prevailing facts and circumstances, is crucial. Preparers and auditors suggest that such a framework could mitigate future regulatory challenges by leveraging foresight. Experts assert that adopting a professional judgment framework enhances the quality and consistency of judgments, ultimately reinforcing trust in principles-based accounting standards.